Manipulation of human history by microbes - Wax, Richard G. (Clin Microbiol Newsl, 2007)
The convergence of the microbial and human worlds provides us with everyday essentials for the survival of our species, and in turn, this interaction brings painful and tragic consequences from pathogens. Looking back, it can be seen that microbes have also changed our history. Were it not for a pathogen that halted an Assyrian military campaign, we might have no Judaism, Christianity, or Islam. Microbes were there to aid adversaries in bringing about the fall of the great Greek and Roman empires. George Washington's bold orders to inoculate the Colonial Army against smallpox (20 years prior to Jenner's discovery of vaccination) were one of the most significant actions in saving the American Revolution from an early and unsuccessful end. Without the yellow fever virus and its accomplice, Aedes aegypti, those living in what was the Louisiana Territory might now have French as their native language. The potato blight caused by Phytophthora infestans changed the histories of both Ireland and those countries (especially the United States) to which victims of the famine emigrated. At the outbreak of World War I, when England was separated from its European source of acetone (needed for the navy's supply of cordite), British citizens had to make do with less gin, but acetone was available thanks to the growth of Clostridium acetobutylicum in those fermentation vessels.